Influences of socio-cultural factors on the writing mindset and grit of the senior high school students in writing academic papers - Pastor, John George P. (Animo Repository, 2022)
This causal, quantitative-descriptive study aimed to analyze the potential influences of socio-cultural factors on the writing mindset and grit of the Senior High School students in writing academic papers and to determine which demographic variables (gender, ethnicity, academic track) predict them. Using the writing mindset scale (Sieben, 2015) and the short grit scale or Grit-S (Duckworth & Quinn, 2009), it was found that the participants’ writing growth mindsets are consistently more superior to their writing fixed mindsets, and their overall grit scores are stable at a somewhat gritty level across all stages of the academic writing process. The responses in the reflection prompts were also analyzed for recurring ideas and some were cited to support or validate the findings of the quantitative data. The results showed that only the participants' ethnicity, not their gender or academic track, was found to be significant in predicting their writing growth mindset, whereas only ethnicity and academic track, but not gender, were significant in predicting their writing fixed mindset when writing academic papers. Lastly, no socio-cultural factor was found to be significant in predicting the participants’ overall grit in writing academic papers. The knowledge that arises out of this investigation asserts that success in the academic writing process is based not only on a person's cognitive abilities, but also on their perceptions of themselves and their writing abilities. Discovering the unknown characteristics of writing mindset and grit could lead to a greater understanding of the nature of self-beliefs and how they interact with learners' individual thinking processes at different stages of the writing process.